Kombinasi AHP-TOPSIS Pada Pemilihan Varietas Unggul Jagung Hibrida Di Desa Pantoan Maju - Hidayati, Lily; Fakhriza, M.; Putri, Raissa Amanda (Universitas Multi Data Palembang, 2025)
The large number of varieties of hybrid corn seeds on the market and farmers' lack of understanding of the characteristics of each variety often make it difficult for farmers to make the right choice according to the conditions of their agricultural land. This is a major challenge for farmer groups in Hamlet III, Pantoan Maju Village, who experience difficulties in selecting superior hybrid corn seed varieties to increase agricultural productivity. To overcome this problem, a web-based decision support system was built that combines the Analytical Hierarchy Process (AHP) method and the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). AHP is used to calculate weights on the criteria used such as crop quality, resistance to pests, and environmental adaptability, while TOPSIS is used to rank preferences for each alternative used. This system is expected to help farmers make more objective and targeted decisions. Test results show that this system is able to provide accurate and relevant recommendations, according to the needs of local farmers. And from the test results of the combination of the two methods, a decision was made on the alternative with the highest preference value of 0.928 from the Bisi-18 corn seed variety.